1995
DOI: 10.1037/0022-0167.42.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Self-concealment and attitudes toward counseling in university students.

Abstract: In study 1 (N = 257 undergraduates) the relations among self-concealment, attitudes toward seeking psychological help, and intentions to seek counseling were explored. Results revealed that even though self-concealment was associated with less favorable attitudes toward seeking help, it was also associated with greater intentions to seek counseling. In Study 2, high and low self-concealers (N = 83) read a description of counseling that either (a) indicated that counseling involves revealing highly personal inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
272
2
19

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(318 citation statements)
references
References 33 publications
25
272
2
19
Order By: Relevance
“…help-seeking studies (see Cepeda-Benito & Short, 1998;Kelly & Achter, 1995;Vogel & Wester, 2003). The zero-order correlations also showed that attitudes were related to intent to seek help for interpersonal, drug, and academic problems.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…help-seeking studies (see Cepeda-Benito & Short, 1998;Kelly & Achter, 1995;Vogel & Wester, 2003). The zero-order correlations also showed that attitudes were related to intent to seek help for interpersonal, drug, and academic problems.…”
Section: Resultsmentioning
confidence: 89%
“…Some studies, for example, have reported that psychological distress and social support do not significantly predict help-seeking intent (Kelly & Achter, 1995;Vogel & Wester, 2003), whereas others show a connection between these factors and intent to seek help (Cepeda-Benito & Short, 1998;Cramer, 1999). Similarly, other studies have demonstrated that certain factors that should decrease or inhibit help seeking, such as the desire to avoid self-disclosing painful feelings or fears about what therapy will be like, affect help-seeking decisions (Kelly & Achter, 1995;Kushner & Sher, 1989;Vogel & Wester, 2003), whereas others do not (Carlton & Deane, 2000;Deane & Todd, 1996). As a result, it is important to directly examine these psychological factors simultaneously with a more sophisticated analysis such as structural equation modeling (SEM).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Deane i Chamberlain 1994;Kelly & Achter 1995;Deane & Todd 1996;Bayer & Peay 1997;Cepeda-Benito & Short 1998;Cramer 1999;Carlton & Deane 2000) nedvosmisleno pokazuju da osobe koji imaju pozitivne stavove prema traženju profesionalne psihološke pomoći snažnije izražavaju nameru da traže pomoć, u odnosu na osobe koje imaju negativne stavove prema traženju profesionalne psihološke pomoći Takođe su značajni i rezultati brojnih istraživanja (npr. Halgin et al 1987;Deane & Todd 1996;Bringle & Byers 1997;Carlton & Deane 2000;Ciarrochi et al 2002) koji pokazuju da je postojeće iskustvo u traženju profesionalne psihološke pomoći pouzdan pokazatelj namere da se profesionalna psihološka pomoć traži i u sadašnjosti, odnosno u budućnosti, ukoliko postoji potreba za njom.…”
Section: Uvodunclassified
“…Among study samples consisting predominantly of White college students, research suggests that individuals with more positive attitudes toward seeking help for mental health problems have greater intentions to seek counselling should the need arise (Cepeda-Benito & Short, 1998;Kelly & Achter, 1995). Notably, the help-seeking attitudes among younger or older youth, in general, have not been widely explored although it is generally believed that most view mental health services negatively (Garland & Zigler, 1994).…”
Section: Factors Relevant To Mental Health Service Deliverymentioning
confidence: 99%